UPAYA PENINGKATAN KEMAMPUAN BERFIKIR KRITIS SISWA MELALUI PENERAPAN MODEL STUDENT FACILITATOR AND EXPALINING - Novika Sakstiwi; Muhammad Syahrul Rizal; Yusnira; Joni; Afriza Rahma Rani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the application of the Student Facilitator and Explaining model and its improvement on the critical thinking skills of class V students of MI Baitul Haq. The research method used is Classroom Action Research (CAR) consisting of two cycles, each with two meetings. Data collection techniques are carried out through teacher observation, student observation, and critical thinking ability tests. The results of the study indicate that the application of the Student Facilitator and Explaining model can improve students' critical thinking skills, indicated by an increase in the average value and percentage of students' classical completion. In cycle II, the second meeting, the average student score reached 8% and classical completion reached 85%, which was previously only 64% with classical completion of 54% in the first meeting. It can be concluded that the Student Facilitator and Explaining model is effective in improving students' critical thinking skills in class V MI Baitul Haq.